Highs and lows of carbohydrate diets - Coyle, E. F. (Sports Science Exchange, 2004)
This brief review attempts to place the confusion about dietary carbohydrate into a logical and, when possible, scientific perspective, with an emphasis on the needs of people who are physically active. Key points: A low-carbohydrate diet in athletes impairs their exercise tolerance and their ability to beneficially adapt to long-term physical training. Physical performance and mood state seem better maintained with a high vs. moderate carbohydrate diet, thus reducing the symptoms of overreaching and possibly overtraining. Adequate dietary carbohydrate is critical to raise muscle glycogen to high levels in preparation for the next days endurance competition or hard training session. Accordingly, during the 24 h prior to a hard training session or endurance competition, athletes should consume 7-12 g of carbohydrate per kilogram of body weight. However, during the 24 h prior to a moderate or easy day of training, athletes need to consume only 5-7 g of carbohydrate per kilogram of body weight. Just as not every day of training should be intense or prolonged, not every day of training requires a high intake of carbohydrate.